Comparison between intubation through ILMA and Airtraq, in different non-conventional patient positions: a manikin study. Issue 1 (23rd December 2010) - Grosomanidis, V; Amaniti, E; Pourzitaki, Ch; Fyntanidou, V; Mouratidis, K; Vasilakos, D
Abstract : Background: Tracheal intubation is often difficult in the prehospital setting, especially in trapped casualties, when long extrication time is anticipated and conventional laryngoscopy cannot be achieved. The aim of the present study was the comparison of applicability and efficacy of two alternative techniques: intubation using a laryngeal mask airway (ILMA) or an Airtraq laryngoscope in different patient positions, using an airway management manikin. Methods: 20 anaesthetists attempted manikin intubations standing behind the manikin (Sup), standing in front and facing the manikin's head (Fac), facing the manikin in the sitting position (Sit) and facing the manikin lying in the lateral decubitus position (Lat), using either Airtraq or ILMA techniques. The intubations were evaluated regarding the success rate, number of attempts and time needed for successful intubation, teeth damage and overall difficulty. Results: All intubation attempts were successful for both techniques. Intubations through ILMA were completed with a significantly greater number of attempts and longer time in the Lat position, compared to Fac, Sit and Sup (p<0.05), whereas intubations using Airtraq in the Sup and Fac positions were completed with a significantly greater number of attempts and longer time, compared to Sit and Lat positions (p<0.05). Both ILMA and Airtraq can be used for securing the airway when direct laryngoscopy is impossible due to patient position. ILMA seems to cause greater difficulty in the Lat position, whereas Airtraq intubation is more easily performed in the Sit and Lat positions. Conclusions: These preliminary data in manikins could indicate the applicability of the methods to the prehospital setting.